Youth internet consumption in Ecuador: indicators of the national digital generation. (10th July 2020) - Rodrigo-Mendizábal, Iván Fernando; Lopez-Jiménez, Daniel Fernando; Arribas-Urrutia, Amaia
This article presents results of youth internet consumption in Ecuador, from the national survey of the World Internet Project - Ecuador. The interest is to determine how the Ecuadorian net generation is linked to the internet, its services, its technologies, its possibilities. It highlights how such a generation shapes a web community that, although it is a consumer, evolves, although not always with the interest of producing content, but as one that moves the technological context - networks, devices, market, etc., - of the internet. Crossed data are presented on the level of access, the places from where it connects to the internet and the preponderance of mobile devices to make personal actions. Among the results it is noted that, although there is internet consumption, the presumption is not yet the vital point of this generation: there is more use of services or connectivity rather than activism, if we think that young people are a fundamental reserve of changes in the information society.